Airborne microbes in five important regions of Chinese traditional distilled liquor (Baijiu) brewing: regional and seasonal variations - Xu, Yan; Qiao, Xue; He, Lei; Wan, Wujie; Xu, Zhongjun; Shu, Xi; Yang, Cheng; Tang, Ya (Frontiers in Microbiology, 2024)
Baijiu is one of the six primary distilled spirits in the world. It is produced through the solid-state fermentation of grains in the open environment, so high-quality Baijiu brewing largely depends on terrior. Environmental microbes are one of the most important factors affecting the quality, quantity, and flavors of Baijiu. As atmosphere is a pool and transport pathway for microbes from the ambient environment to Baijiu brewing ecosystems, we explored the functional microbes of Baijiu brewing in five important regions. The regions fell into two topographical types, namely, plain and river-valley. In total, 41 functional microbes were identified rich (relative abundance >0.1%) in at least one of the regions, such as the fungi of Aspergillus, Candida, Cladosporium, Debaryomyces, Penicillium, Pichia, Rhizopus, Saccharomyces, and Wickerhamomyces) and the bacteria of Acetobacter, Bacillus, Clostridium, Enterobacter, Lactobacillus, Methanosarcina, Methanobacterium, Methanobrevibacter, and Pseudomonas. However, some functional bacteria (e.g., Clostridia, Gluconacetobacter, and Weissella) and fungi (e.g., Dekkera, Eurotium, Issatchenkia, Mucor, and Phoma) were not rich or were not detected in the atmosphere. Airborne microbiomes and the Phylogenetic Diversity (PD) index were significantly different between the main brewing season (winter) and the summer break in each region, except for the fungi in one region. In winter, airborne microbiomes were significantly different among almost all the regions. The relative abundance of bacterial fermentation function in each region increased from summer to winter. The relative abundances of fungal yeast function were higher in winter for the plain regions but were higher in summer for the river-valley regions. In sum, our results suggested that: (1) atmosphere was one but not the sole important source of functional microbes for Baijiu brewing and (2) microbiomes in different regions might be quite different but they could share some major functions related to Baijiu brewing.